Comparison of the corrosion behaviour of laser-annealed Ni–P and Ni–Mo–P deposits in H2SO4 and NaCl solutions. (3rd March 2016) - Liu, H.; Wang, P.; Liu, Z.; Harrison, G.; Thompson, G. E.
Abstract : The corrosion behaviour of electroless amorphous Ni–P and Ni–Mo–P deposits before and after laser treatment was systemically compared using potentiodynamic polarisation and electrochemical impedance spectroscopy (EIS) techniques, and X-ray and SEM/EDS analysis and interferometry. EIS studies in 3.5 wt-% NaCl solution indicate that a suitable laser treatment can strongly improve the pitting corrosion resistance of the Ni–Mo–P deposit to Cl – attack compared with the Ni–P deposit and the best corrosion resistance of the Ni–Mo–P deposit appears at a laser scanning velocity of 12 mm s −1 . In 0.5 M H2 SO4 solution, the corrosion mechanism of the Ni–Mo–P deposit is mainly associated with the dissolution of Mo from Ni–Mo solid solution. The as-plated Ni–Mo–P deposit exhibits better corrosion resistance than the Ni–P deposit, and this is true for the laser-treated Ni–Mo–P deposit at a laser scanning velocity <10 mm s −1 .